39.7k views
7 votes
I want to solve these mathematical equations

2t-✓2= 3t+✓2. Number 1
(-x+2✓3)(-3x-✓2) =0 number 2

User Ivo Sabev
by
5.0k points

2 Answers

13 votes

Answer:

which class you read now

User Touhami
by
5.7k points
10 votes

Answer:

see explanation

Explanation:

Given

2t -
√(2) = 3t +
√(2) ( add
√(2) to both sides )

2t = 3t + 2
√(2) ( subtract 3t from both sides )

- t = 2
√(2) ( multiply both sides by - 1 )

t = - 2
√(2)

-----------------------------------------------------------

Given

(- x + 2
√(3) )(- 3x -
√(2) ) = 0

Equate each factor to zero and solve for x

- x + 2
√(3) = 0 ( subtract 2
√(3) from both sides )

- x = - 2
√(3) ( multiply both sides by - 1 )

x = 2
√(3)

- 3x -
√(2) = 0 ( add
√(2) to both sides )

- 3x =
√(2) ( divide both sides by - 3 )

x = -
(√(2) )/(3)

User Nathan Colgate
by
5.2k points